Spectral optical properties of long-range transport Asian dust and pollution aerosols over Northeast Asia in 2007 and 2008 - J. Jung; Y. J. Kim; K. Y. Lee; M. G. -Cayetano; T. Batmunkh; J.-H. Koo; J. Kim (Atmospheric Chemistry and Physics, 2010)
As a part of the IGAC (International Global Atmospheric Chemistry) Mega-cities program, aerosol physical and optical properties were continuously measured from March 2007 to March 2008 at an urban site (37.57° N, 126.94° E) in Seoul, Korea. Spectral optical properties of long-range transported Asian dust and pollution aerosols have been investigated based on the year long measurement data. Optically measured black carbon/thermally measured elemental carbon (BC/EC) ratio showed clear monthly variation with high values in summer and low values in winter mainly due to the enhancement of light attenuation by the internal mixing of EC. Novel approach has been suggested to retrieve the spectral light absorption coefficient (babs) from Aethalometer raw data by using BC/EC ratio. Mass absorption efficiency, σabs (=babs/EC) at 550 nm was determined to be 9.0±1.3, 8.9±1.5, 9.5±2.0, and 10.3±1.7 m2 g−1 in spring, summer, fall, and winter, respectively with an annual mean of 9.4±1.8 m2 g−1. Threshold values to classify severe haze events were suggested in this study. Increasing trend of aerosol single scattering albedo (SSA) with wavelength was observed during Asian dust events while little spectral dependence of SSA was observed during long-range transport pollution (LTP) events. Satellite aerosol optical thickness (AOT) and Hysplit air mass backward trajectory analyses as well as chemical analysis were performed to characterize the dependence of spectral optical properties on aerosol type. Results from this study can provide useful information for studies on regional air quality and aerosol's effects on climate change.